Analisis Perbandingan Daya Dukung Dan Penurunan Pondasi Bored Pile Berdasarkan Data SPT - Tahismasari, Santy; Darmiyanti, Lydia; Rodji, Achmad Pahrul (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2024)
Foundation is part of the lower structure (sub structure), which has a very important role in carrying the load of the upper structure as a result of the forces that occur in the upper structure, such as wind forces, earthquake forces and the weight of the structure self. The purpose of the analysis is to determine the bearing capacity analysis using the Reese & Wright (1977) and plaxis 2d methods, for settlement analysis using the vesic and plaxis 2d methods based on the results of SPT. Based on the SPT data, the results of manual calculations using the Reese & Wright method (1977) are 164,64 kN while calculations using plaxis 2D software are 375,42 kN. The settlement obtained by manual calculations by Vesic nethod is 2,873 cm, while the results of calculations in Plaxis 2D software are 0,578 cm. Based on the results of calculating the bearing capacity of drilled pile foundations when compared with the Reese & Wright (1977) method, it provides the most economical results compared to Plaxis 2D calculations. From the analysis results, these calculations are in accordance with SNI 8460 of 2017